PROGESTERONE, METABOLITES AND MINERALS IN ANESTRUS, SUBESTRUS, REPEAT BREEDING AND CYCLIC COWS
A comparative field study on serum profile of progesterone (p4) and metabolites of 21 anestrus, 10 subestrus, 31 repeat breeding and 8 normal cyclic crossbred cows revealed that the serum P4 was significantly (P<0.01) higher in subestrus cows than in the anestrus and repeat breeders and even normal cyclic cows. The serum total protein was significantly (P<0.01) lower in repeat breeders and normal cyclic cows than in anestrus and subestrus cows. The cholesterol was significantly P<0.05) lower in animals with all three reproductive disorders as compared to normal cyclic ones. The calcium was significantly (P<0.01) lower in anestrus and repeat breeding cows than in subestrus and normal cyclic cows, but the trend of inorganic phosphorus was reversed, the subestrus and repeat breeding cows had significantly higher serum inorganic phosphorus level as compared to normal cyclic cows. The serum magnesium was significantly P<0.05) higher in normal cyclic cows than that in all three categories of infertile animals. Among the trace minerals, zinc content was significantly (P<0.05) higher in anestrus and repeat breeders than the subestrus and normal cyclic cows, whereas iron content was higher in anestrus and subestrus cows. The serum levels of copper, cobalt and manganese did not show any variation among the normal cyclic and other three treatment groups of infertile cows. These findings suggested the importance of these elements in maintaining normal reproductive rhythm of dairy cows. , number=2, journal=The Indian Journal of Animal Reproduction, author=KUMAR, RAJESH and BUTANI, M G and DHAMI, A J and KAVANI, F S and PATEL, M D and SHAH, R J, year=2023, month=Jan., pages=19–22